GENDHING NDADI Musik dalam Angguk Non-Cerita di Kebumen - Rabimin Rabimin (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2002)
This point focuses on the explanation of musicality context that is generated by supernatural creed called ndadiin the Angguk folk art in the villages of Kebumen. It is intended to show the typicality of the musical environment.